Optical glass-ceramics based on nanosized crystals of magnesium aluminate spinel doped with iron ions. (December 2020) - Bukina, V; Dymshits, O; Alekseeva, I; Tsenter, M; Zapalova, S; Khubetsov, A; Zhilin, A; Basyrova, L; Volokitina, A; Serres, J M; Mateos, X; Loiko, P
Abstract: Transparent glass-ceramics of magnesium aluminum silicate system based on nanosized MgAl2O4 spinel crystals nucleated by TiO2 and doped with Fe2 O3 were developed. Their structure and spectroscopic properties were studied. The glass-ceramics are important as reference samples in development of saturable absorbers in the short-wave infrared spectral range (2-3 μm).